Highly selective approach for the total synthesis of (+)-heliconol A - Mohapatra, Debendra K.; Chatterjee, Bhaskar; Gurjar, Mukund K. (Tetrahedron-Asymmetry, 2008)
The total synthesis of heliconol A, a representative of a new class of polyketide-derived hemiketals containing a reduced furanocyclopentane unit, has been achieved via the stereoselective reduction of a ketone, the face selective dihydroxylation, a Sonogashira coupling reaction, and a cis-selective reduction as the key steps. (C) 2008 Elsevier Ltd. All rights reserved.

Highly stereoselective approach toward the synthesis of the macrolactone core of amphidinolide W - Mohapatra, Debendra K.; Chatterjee, Bhaskar; Gurjar, Mukund K. (Tetrahedron Letters, 2009)
The diastereoselective synthesis of the macrolactone core of amphidinolide W was successfully accomplished using Evans' asymmetric alkylation, Aldol reaction, Julia-Kocienski olefination, and Kita's macrocyclization protocol. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide W; Evans aldol; Evans alkylation; Julia-Kocienski olefination; Kita's macrocyclization